New Horizons in Artificial Intelligence in Libraries - Edmund Balnaves; Leda Bultrini; Andrew Cox; Raymond Uzwyshyn (De Gruyter Saur, 2024)
There is increasing use of AI technologies in many aspects of library operations and types of libraries. This ranges across public, national, research, academic and special libraries and includes public and reference services, automated classification, special and research collections, archives and customer service through chatbots and discovery systems. Vendors are also adding elements of AI in new and existing library products including search and discovery and research platforms and recommender systems. The role and impact of AI present opportunities and challenges and open future possibilities. IT plays a significant role in the development and use of AI technologies, but ethical considerations and wider organizational thinking must also play an equally significant role. AI's uses can have considerable impact and possible unintended consequences on library operations and services and wider societal implications. All of this is considered in this both pragmatic and wider philosophical text. This publication provides an opportunity to explore developing new library AI paradigms, including present use case practical implementation and opportunities on the horizon as well as current large ethics questions and needs for transparency, scenario planning, considerations and implications of bias as library AI systems are developed and implemented presently and for our collective future.